2019
DOI: 10.5455/medarh.2019.73.351-355
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists' Attitudes and Role in Diabetes Management in Bosnia and Herzegovina

Abstract: Introduction: Diabetes is the fastest growing chronic diseases worldwide and in Bosnia and Herzegovina. International standards for diabetes care have recognized the crucial role of pharmacists in diabetes management. Community pharmacists can provide services beyond medication dispensing inducing patient identification, assessment, education, referral, monitoring and behavioral counseling. Pharmacists' attitudes toward diabetes are generally positive but do not correlate with the degree of their involvement i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This data highlights a need for comprehensive capacity building including multiple CPDs and post-CPD follow-up to promote adherence with quality standards for pharmacy professionals in Southeast Asia to ensure that they are well positioned to recognize potential symptoms of disease and to provide comprehensive and accurate information on self-management practices, particularly as people living with diabetes often approach their pharmacy for information on a range of topics related to diabetes, as shown by our survey. Consistent with our findings, previous studies in other countries have highlighted gaps in pharmacists’ diabetes-related knowledge, highlighting the importance of continuing education [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…This data highlights a need for comprehensive capacity building including multiple CPDs and post-CPD follow-up to promote adherence with quality standards for pharmacy professionals in Southeast Asia to ensure that they are well positioned to recognize potential symptoms of disease and to provide comprehensive and accurate information on self-management practices, particularly as people living with diabetes often approach their pharmacy for information on a range of topics related to diabetes, as shown by our survey. Consistent with our findings, previous studies in other countries have highlighted gaps in pharmacists’ diabetes-related knowledge, highlighting the importance of continuing education [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…Diabetes is significant health problem in Bosnia and Herzegovina (B&H), and based on IDF Atlas 2017 it is estimated that there are more than 366 thousands adults with diabetes in B&H with prevalence of 12.5% ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of the health care responders were barangay health workers, often referred to as Community Health Workers (De la Cruz et al., 2019). The health care professionals from the Philippines, previous research involving nursing students (Williamson et al., 1996), and pharmacists from Bosnia and Herzegovina (Catic et al., 2019) indicated survey participants agree that caring for patients with diabetes requires specialized training. The rank‐ordered subscales for the nursing students who attended the various nursing schools are in Table 2.…”
Section: Discussionmentioning
confidence: 95%
“……support from family and friends is important in dealing with diabetes. students (Williamson et al, 1996), and pharmacists from Bosnia and Herzegovina (Catic et al, 2019) indicated survey participants agree that caring for patients with diabetes requires specialized training.…”
mentioning
confidence: 99%